Analysis of fatal cases of severe fever with thrombocytopenia syndrome in Jiangsu province, China, between 2011 and 2022: A retrospective study - Liang, Shuyi; Xie, Wei; Li, Zhifeng; Zhang, Nan; Wang, Xiaochen; Qin, Yuanfang; Bao, Changjun; Hu, Jianli (Frontiers in Public Health, 2023)
Introduction Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease caused by the SFTS virus (SFTSV), which has a high fatality rate. This disease has become increasingly prevalent in recent years in Jiangsu province, with a noticeable rise in its incidence. Notably, fatal cases have also been increasing. Our study aimed to analyze the epidemiological characteristics and risk factors associated with the fatal cases of SFTS in Jiangsu province from 2011 to September 2022. Methods A retrospective study was performed among 698 SFTS cases during 2011-2022 in Jiangsu Province, China. Cox regression analyses were used to determine the dependent and independent risk factors that affected patient survival time. ArcGIS 10.7 was used for the visualization of the geographical distribution of the deaths from SFTS. Results There were 698 SFTS cases reported, with an increasing incidence, over the 12-year period. Among these cases, 43 deaths were reported. Fatal cases of SFTS were reported in 12 district counties from 2011 to 2022. Notably, most of the deaths occurred in Lishui county of Nanjing City. The median age of those who died was 69 years, with age ranges from 50 to 83 years. Multivariable Cox regression analysis showed that older age (>70) and living in Lishui county were risk factors for death from SFTS in Jiangsu province. Therefore, older adults aged over 70 years and residing in Lishui county were the high-risk group for SFTS mortality. Discussion Over the past 12 years, we have observed a consistent rise in the incidence of SFTS, accompanied by a relatively high case fatality rate, making it a critical public health issue. Therefore, it is urgently necessary to study the impact of meteorological factors on SFTS epidemics and devise prevention and control strategies.